Texture and elastic anisotropy of a mylonitic anorthosite from the Morin Shear Zone (Quebec, Canada). (February 2015) - Gómez Barreiro, Juan; Wenk, Hans-Rudolf; Vogel, Sven
Abstract: A sample of anorthosite from the granulite facies Morin Shear Zone (Quebec, Canada) was investigated for crystal preferred orientation and elastic anisotropy. Time-of-flight neutron diffraction data obtained with the HIPPO diffractometer at LANSCE were analyzed with the Rietveld method to obtain orientation distribution functions of the principal phases (plagioclase, clinopyroxene and orthopyroxene). Texture and microstructures are compatible with the plastic deformation of the aggregate under high-T conditions. All mineral phases depict a significant preferred orientation that could be related to the general top-to-the north shearing history of the Morin Shear Zone. Texture patterns suggest that (010)[001] in plagioclase and (110)[001] in clinopyroxene are likely dominant slip systems. Using preferred orientation data P- and S-waves velocities and elastic anisotropy were calculated and compared with previous studies to explore elastic properties of rocks with different pyroxene-plagioclase mixtures. P-wave velocity, S-wave splitting and anisotropy increase with clinopyroxene content. Seismic anisotropy is linked to the texture symmetry which can lead to large deviations between actual anisotropy and that measured along Cartesian XYZ sample directions (lineation/foliation reference frame). This is significant for the prediction and interpretation of seismic data, particularly for monoclinic or triclinic texture symmetries. Highlights: Plagioclase–Pyroxene quantitative texture analysis. Time-of-flight neutron diffraction. Morin Shear Zone (Grenville Province). Seismic anisotropy of metabasites.